The Generalized Stability of an n-Dimensional Jensen Type Functional Equation: J. Tipyan, C. Srisawat, P. Udomkavanich, P. Nakmahachalasint - Team, Support (Thai Journal of Mathematics, 2014)
In this paper, we will investigate the generalized Hyer-Ulam-Rassias stability of an n-dimensional functional equation, where n > 1 is an integer, and p1,..., pn are positive real number with